An update on animal models of liver fibrosis - Wu, ShuTing; Wang, XinXin; Xing, WenBo; Li, FenYao; Liang, Ming; Li, KeShen; He, Yan; Wang, JianMing (Frontiers in Medicine, 2023)
The development of liver fibrosis primarily determines quality of life as well as prognosis. Animal models are often used to model and understand the underlying mechanisms of human disease. Although organoids can be used to simulate organ development and disease, the technology still faces significant challenges. Therefore animal models are still irreplaceable at this stage. Currently, in vivo models of liver fibrosis can be classified into five categories based on etiology: chemical, dietary, surgical, transgenic, and immune. There is a wide variety of animal models of liver fibrosis with varying efficacy, which have different implications for proper understanding of the disease and effective screening of therapeutic agents. There is no high-quality literature recommending the most appropriate animal models. In this paper, we will describe the progress of commonly used animal models of liver fibrosis in terms of their development mechanisms, applications, advantages and disadvantages, and recommend appropriate animal models for different research purposes.